2021
DOI: 10.1038/s41598-021-93648-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation and extinction of laminar diffusion flame induced by external acoustic wave and source

Abstract: Acoustic wave can destabilize the flame and has a potential in firefighting, but the influences of the sound source and its frequency are still poorly understood. This work applies a loudspeaker to extinguish a laminar diffusion propane flame of 5–25 mm high, where the local sound frequency is 50–70 Hz and sound pressure is 0.8–3.2 Pa (92.0–104.1 dB). Results reveal a constant flame pulsating displacement at the extinction limit, independent of the sound environment used. Such a flame pulsating displacement is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Bennewitz et al [12] studied the extinction mechanism for a single droplet flame in acoustic standing waves and found that extinction was caused by the temporal increase in the local rate of normal flame strain. This extinction mechanism was also supported by Xiong et al [13][14][15][16]; they further modified the Damköhler number (Da), suitable for acoustic extinction, and the flaming firebrand. Furthermore, droplets can be extinguished when the value of Da drops below 1.0.…”
Section: Introductionmentioning
confidence: 64%
“…Bennewitz et al [12] studied the extinction mechanism for a single droplet flame in acoustic standing waves and found that extinction was caused by the temporal increase in the local rate of normal flame strain. This extinction mechanism was also supported by Xiong et al [13][14][15][16]; they further modified the Damköhler number (Da), suitable for acoustic extinction, and the flaming firebrand. Furthermore, droplets can be extinguished when the value of Da drops below 1.0.…”
Section: Introductionmentioning
confidence: 64%
“…To obtain flame fluctuations, the Otsu threshold is used to generate binarized images of 2000 frames for each operating condition (boundaries of all 2000 frames are shown simultaneously in Figure 7 for methane and airflow rates of 0.200 and 3 𝑠𝑙𝑝𝑚, respectively). The mean center of gravity (𝑥 𝐶𝐺,𝑚𝑒𝑎𝑛 , 𝑦 𝐶𝐺,𝑚𝑒𝑎𝑛 ), length (𝐿 𝑚𝑒𝑎𝑛 ), and width (𝑊 𝑚𝑒𝑎𝑛 ) are determined; then, the standard deviation is then used to calculate the flame's pulsating displacement in terms of the flame's center of gravity, length, and width [28]: (5)…”
Section: Flame Characteristicsmentioning
confidence: 99%
“…Because of high energy density of hydrocarbon fuels, combustion-based micro-power devices are a more attractive option for portable power generation than rechargeable batteries [18][19][20][21][22]. In these systems, swirling flows are one method for flame stabilization [23][24][25][26][27][28][29][30]. To the best of authors' knowledge, there has never been research on the effects of swirl number on turbulent flame dynamics and characteristics by taking advantage of threshold-based image segmentation method.…”
Section: Introductionmentioning
confidence: 99%
“…Xiong et al [15] found that the effectiveness of acoustic wave extinguishment decreased with increasing dripping velocity. They [16] also discovered the use of acoustic waves to extinguish propane flames and found that the frequency and sound pressure of the acoustic source had a significant effect on the flame. Lower-frequency acoustic sources produced larger membrane vibrations and flame flicker displacements, promoting flame extinction.…”
Section: Introductionmentioning
confidence: 99%